تقييم كفاءة النظام الضريبي في سورية باستخدام مؤشرات V. Tanzi دراسة تطبيقية - الضابط, مدين (Latakia University Journal - Economic and Legal Sciences Series, 2019)
This search aims to study the efficiency of the Syrian tax system using the indicators of V. Tanzi. It is based on eight key indicators: concentration, dispersion, erosion, collection lags, specificity, objectivity, enforcement and cost of collection. The logical answers to these indicators provide an assessment of the effectiveness of the country's tax system. Research tools such as observation and interviews, which included many tax administration personnel and taxpayers alike, were relied on. The results of this research showed a severe weakness in the efficiency of the tax system in Syria in terms of weak concentration, increasing dispersion and continuous erosion due to the narrow tax base and the implementation of the qualitative tax system, which has been abandoned by most countries. In addition to the increase in the volume of tax accumulation, the lack of quality, the severe weakness in the tax revenues because of the loss of objectivity in the taxation, the weakness of the tax administration, and the absence of a deterrent system with a clear bill of rights for the taxpayers, which deepened the lack of compliance and loss of trust between the tax administration and taxpayers. In light of the above, the study concluded with a set of recommendations that, if implemented, could improve the efficiency of the tax system and identify priorities for reform. يهدف هذا البحث إلى دراسة مدى كفاءة النظام الضريبي السوري باستخدام مؤشرات V. Tanzi. وتقوم على ثمانية مؤشرات أساسية هي: التركيز والتشتت والتآكل والتراكم الضريبي أو تأخر التحصيل والنوعية والموضوعية والإلزام وتكلفة فرض الضرائب. تتيح الإجابات المنطقية بتطبيق تلك المؤشرات تقييم فعالية النظام الضريبي لبلد معين. وقد تم الاعتماد على أدوات بحثية كالملاحظة والمقابلات الشخصية، والتي شملت العديد من العاملين في الإدارة الضريبية، والمكلفين بالضريبة على حد سواء. وقد أظهرت نتائج هذا البحث الضعف الشديد في كفاءة النظام الضريبي في سورية لجهة ضعف التركيز وزيادة التشتت وحدوث تآكل مستمر بسبب ضيق القاعدة الضريبية وتطبيق نظام الضرائب النوعي الذي تخلت عن تطبيقه معظم دول العالم، وزيادة حجم التراكم الضريبي، وغياب النوعية على حساب القيمة مفسرة العقلية الجبائية للإدارة الضريبية، مع الضعف الشديد على مستوى الحصيلة لفقدان الموضوعية في التكليف وضعف الإدارة الضريبية وغياب نظام عقوبات رادع مع شرعة حقوق واضحة للمكلفين، الأمر الذي عمق من حالة عدم الالتزام وفقدان الثقة بين الإدارة الضريبية والمكلفين. وفي ضوء ما سبق، خلصت الدراسة إلى مجموعة من التوصيات التي يمكن، في حال تطبيقها، أن تحسن من كفاءة النظام الضريبي، وتحدد أولويات الإصلاح.